Fluorochemicals from fluorspar via a phosphate-enabled mechanochemical process that bypasses HF - Patel, C; André-Joyaux, E; Leitch, JA; de Irujo-Labalde, XM; Ibba, F; Struijs, J; Ellwanger, MA; Paton, R; Browne, DL; Pupo, G; Aldridge, S; Hayward, MA; et al. (American Association for the Advancement of Science, 2023)
All fluorochemicals—including elemental fluorine and nucleophilic, electrophilic, and radical fluorinating reagents—are prepared from hydrogen fluoride (HF). This highly toxic and corrosive gas is produced by the reaction of acid-grade fluorspar (>97% CaF2) with sulfuric acid under harsh conditions. The use of fluorspar to produce fluorochemicals via a process that bypasses HF is highly desirable but remains an unsolved problem because of the prohibitive insolubility of CaF2. Inspired by calcium phosphate biomineralization, we herein disclose a protocol of treating acid-grade fluorspar with dipotassium hydrogen phosphate (K2HPO4) under mechanochemical conditions. The process affords a solid composed of crystalline K3(HPO4)F and K2−xCay(PO3F)a(PO4)b, which is found suitable for forging sulfur-fluorine and carbon-fluorine bonds.